Ecological dumping and environmental capital flight: The economics behind the propaganda - Michael Kuhn; Thusnelda Tivig (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
In this paper we analyze the connection between ecological dumping and environmental capital flight which in the literature is presented in three versions: capital flees in order to ecologically dump, firms flee and thus ecologically dump, and capital flees because governments ecologically dump. We find that 'ecological dumping' describes an ill posed problem: it has little to do with dumping and need not have any impact on the environment. Looking at the existing literature we find that although 'capital flight' is a misnomer, too, there are real problems dealt with under this heading. Nevertheless, because of their emotive and misleading undertone, we should better give up both notions.
Keywords: F13; F21; H73; Q28; 330; Dumping; Capital Flight; Delocation; Environment; Umweltpolitik; Dumping; Standortfaktor; Internationaler Wettbewerb; Kapitalflucht; Theorie